2020
DOI: 10.1002/ijgo.13312
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of precancerous cervical lesions among HIV‐positive women in Jos, north‐central Nigeria

Abstract: Objective: To determine the prevalence and predictors of precancerous cervical lesions among HIV-positive women in Jos, Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
5
8
3
Order By: Relevance
“…There are varying results reported in previous studies that examined the association between age and cervical cytological abnormalities among WLHIV. In similarity to our study, findings from the study by Daniel et al [16] in Jos, Nigeria, and Kafuruki et al [30] in Mwanza-Tanzania, reported no association between age and cervical cytological abnormalities, while others conducted by Ononogbu et al [31] in Abuja, Nigeria, Kassa et al [32] in Amhara Region, Northwest Ethiopia, found that age was a significant predictor for cervical epithelial changes. The variations reported across these various studies including the current study concerning the association between age and cervical epithelial abnormalities could therefore be attributed to the residual effects of other confounding factors which may or may not be adequately controlled for during statistical analyses.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…There are varying results reported in previous studies that examined the association between age and cervical cytological abnormalities among WLHIV. In similarity to our study, findings from the study by Daniel et al [16] in Jos, Nigeria, and Kafuruki et al [30] in Mwanza-Tanzania, reported no association between age and cervical cytological abnormalities, while others conducted by Ononogbu et al [31] in Abuja, Nigeria, Kassa et al [32] in Amhara Region, Northwest Ethiopia, found that age was a significant predictor for cervical epithelial changes. The variations reported across these various studies including the current study concerning the association between age and cervical epithelial abnormalities could therefore be attributed to the residual effects of other confounding factors which may or may not be adequately controlled for during statistical analyses.…”
Section: Discussionsupporting
confidence: 89%
“…Among behavioural factors weakening the immune system, smoking appeared to strongly increase the risk of cervical precancer and cancer [35][36][37]; however, there is an interplay of multiple factors concerning smoking and cervical carcinogenesis, especially by direct local carcinogenic effect and local immunosuppression [32]. It is therefore almost always difficult to isolate the epidemiologic contribution of smoking to cervical carcinogenesis as confirmed in our current study and other recent studies that found no independent correlation between smoking and cervical precancer and/or cancer [16,32]. Nonetheless, smoking should always be considered in clinical practice and research concerning cervical precancer and cancer.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The present study was focused on the women who came for cervical cancer screening at various screening sites in the state, while the study subjects Dim were controlled for an HIV study at a facility. The same study by Dim found a prevalence of 12.6% among HIV-positive women at the health facility which is similar to the 12.2% [29] prevalence reported by Daniel et al in 2020 in Jos Nigeria among HIV-positive women.…”
Section: Discussionsupporting
confidence: 81%